Two new species of the genus Dasybasis Macquart, 1847, from Chile (Diptera: Tabanidae: Diachlorini) - González, Christian R. (Zootaxa, 2014)
The females of Dasybasis antillanca and Dasybasis collagua, new species, are described from specimens collected in Osorno and Iquique Provinces, south and north Chile, respectively. Their relationships to other Dasybasis species are discussed.